Yamabe flow: Steady solitons and Type II singularities. (August 2018) - Choi, Beomjun; Daskalopoulos, Panagiota
Abstract: We study the convergence of complete non-compact conformally flat solutions to the Yamabe flow to Yamabe steady solitons. We also prove the existence of Type II singularities which develop at either a finite time T or as t → + ∞ .